Tobacco Smoking: Findings from 20 Years of the Tehran Lipid and Glucose Study - Parizadeh, Donna (Int J Endocrinol Metab, 2018)
CONTEXT: Smoking is a global public health priority and accurate data of the local population is essential to improve the health policies against its use. Hence, this study aimed to summarize the important findings available on the prevalence of smoking and its association with non-communicable diseases, documented by one of the largest prospective community-based studies of Iran. EVIDENCE ACQUISITION: All articles derived from the Tehran Lipid and Glucose Study (TLGS) in the last two decades, from the earliest publications until 30 January 2018 were reviewed for their findings on tobacco smoking. RESULTS: The prevalence of smoking in non-diabetic adults ≥ 20 years increased between baseline (phase I, 1999 - 2001) and follow-up (phase V, 2008 - 2011) from 25.5% to 35.4% among men and from 3.4% to 6.8% among women. In TLGS adolescents (10 - 18 years) water pipe use increased between 2003 and 2005 from 35.5% to 40.9% among boys and from 19.7% to 26.1% among girls. Regarding health hazards, smoking in men was associated with increased risk of combined impaired fasting glucose/impaired glucose tolerance [hazard ratio (HR) 1.69; confidence interval (CI) 95% 1.15 - 2.48] and hypertension (HR 1.26; CI 95% 0.98 - 1.63). Moreover, men, even smoking less than 10 cigarettes per day, were at increased risk for cardiovascular diseases by HR 2.12 (CI 95% 1.14 - 3.95). For women, the risk of chronic kidney disease dramatically increased 5.74-fold (CI 95% 2.71 - 12.15) among smokers. In the whole population, smoking contributed to 7.7% of all-cause mortality with HR 1.75 (CI 95% 1.38 - 2.22). Other health aspects of tobacco smoke, including its impact on metabolic status, thyroid function, female reproductive system and life style have also been reviewed. CONCLUSION: Considering hazards of smoking, there is the urgency for more effective preventive measures in Iran; emphasizing the need for further local studies on the hazards of smoking with special attention to women and adolescents and the independent hazards of water pipe use.